Implementasi Pengendalian Inventory Pada PT.X - Kevin Joshua Harianto; Yulia Yulia; Rudy Adipranata (Jurnal Infra, 2021)
Inventory control is a process to ensure the amount of supply available in a business process. Inventory control can help prevent losses in managing raw materials and also setting up the warehouse system at PT.X. Based on the problems that occur at PT.X, a method that can be systemized with warehouse systems and production results is needed, with the aim of finding the average of sales per day and month which is useful for re-ordering, and also for analyzing so that there is no stockout. Reports for each transaction period can be viewed on the system in accordance with the recording of transaction data. The data used in calculating the Economic Order Quantity and Reorder Point are transactions from 2019 at the warehouse of PT. X.